Synthesis of 2, 6‐Di(pyrazol‐1‐yl)pyrazine Derivatives and the Spin‐State Behavior of Their Iron(II) Complexes. Issue 5 (4th December 2012) - Mohammed, Rufeida; Chastanet, Guillaume; Tuna, Floriana; Malkin, Tamsin L.; Barrett, Simon A.; Kilner, Colin A.; Létard, Jean‐François; Halcrow, Malcolm A.
Abstract: Chlorination of 2, 6‐bis(pyrazol‐1‐yl)pyrazine (bppz) with NaClO in acetic acid afforded 2, 6‐bis(4‐chloropyrazol‐1‐yl)pyrazine ( L 2 Cl). 2, 6‐Bis(4‐bromopyrazol‐1‐yl)pyrazine ( L 2 Br), 2, 6‐bis(4‐iodopyrazol‐1‐yl)pyrazine ( L 2 I), 2, 6‐bis(4‐methylpyrazol‐1‐yl)pyrazine ( L 2 Me), and 2, 6‐bis(4‐nitropyrazol‐1‐yl)pyrazine ( L 2 NO2 ) were also prepared by reactions of the preformed 4‐substituted pyrazoles with 2, 6‐dichloropyrazine. The reduction of L 2 NO2 with iron powder gave 2, 6‐bis(4‐aminopyrazol‐1‐yl)pyrazine ( L 2 NH2 ) and L 2 I was converted into 2, 6‐bis[4‐(phenylethynyl)pyrazol‐1‐yl]pyrazine ( L 2 CCPh) by a Sonogashira coupling reaction. The salts [Fe( L 2 Me)2 ]X2 (X – = BF4 – and ClO4 – ) underwent thermal spin‐crossover abruptly at around 200 K in one and two steps, respectively. The [Fe( L 2 Me)2 ]X2 salts exhibited different light‐induced excited spin‐state trapping (LIESST) behavior; the BF4 – salt behaves classically [ T (LIESST) = 93 K], but the ClO4 – salt undergoes a multistep LIESST relaxation. In contrast, solid [Fe( L 2 Cl)2 ][BF4 ]2 adopts a fixed 2:1 high/low‐spin‐state population that does not change with temperature below 300 K, whereas [Fe( L 2 Br)2 ][BF4 ]2 and [Fe( L 2 I)2 ][BF4 ]2 form low‐spin solvated crystals that are transformed into high‐spin powders on drying. The pyrazinyl group in the L 2 R ligands slightly stabilizes the low‐spin state of the complexes, as determined by solution‐phase magnetic measurements. The crystal structure of [Fe( L 2 CCPh)(OH2 ) z ][BF4 ]2 contains a disordered mixture of six‐ ( z = 3) and seven‐coordinate ( z = 4) iron centers. Abstract : Seven 2, 6‐di(pyrazol‐1‐yl)pyrazines substituted at the pyrazole 4‐positions, and some of their iron complexes, are presented. The solid‐state complexes exhibit various spin‐state behaviors, including high spin, temperature‐invariant mixed spin, thermal spin‐crossover, and the LIESST effect. In solution, the pyrazinyl ligands slightly stabilize the low‐spin states of the compounds.